The emerging production networks in Mekong region. (21st January 2014) - Taguchi, Hiroyuki; Matsushima, Daisuke; Hayakawa, Kazunobu
This paper set out to examine the recent evolution of the production networks through the fragmentation in the Mekong region within ASEAN by using trade data and micro–data of Japanese multinational enterprises. Our main findings are as follows. First, the fragmentation momentum in the Mekong region within ASEAN could be identified from the rise in intra–Mekong trade of machinery parts and components, especially in the growth of their two–way trade between Thailand and Vietnam. Second, the 'agglomeration of fragments' could be observed from the high correlation and some causality of the manufacturing sales trends between industrial estates in Thailand and Vietnam.